2021
DOI: 10.1186/s12966-021-01144-5
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness analysis of a multiple health behaviour change intervention in people aged between 45 and 75 years: a cluster randomized controlled trial in primary care (EIRA study)

Abstract: Background Multiple health behaviour change (MHBC) interventions that promote healthy lifestyles may be an efficient approach in the prevention or treatment of chronic diseases in primary care. This study aims to evaluate the cost-utility and cost-effectiveness of the health promotion EIRA intervention in terms of MHBC and cardiovascular reduction. Methods An economic evaluation alongside a 12-month cluster-randomised (1:1) controlled trial conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Van der Bruggen et al [ 15 ] suggested in a large modelling study that offering lifestyle interventions to people at risk could be cost-effective, in contrast to offering the intervention to the full population. However, our study showed—in line with the EIRA trial [ 17 ]—similar (CVRM-related) costs and similar or worse QALYs in the intervention period compared to the control period. The lower utilities in our intervention period may be partly explained by the stepped-wedge design, which may have induced selection bias.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Van der Bruggen et al [ 15 ] suggested in a large modelling study that offering lifestyle interventions to people at risk could be cost-effective, in contrast to offering the intervention to the full population. However, our study showed—in line with the EIRA trial [ 17 ]—similar (CVRM-related) costs and similar or worse QALYs in the intervention period compared to the control period. The lower utilities in our intervention period may be partly explained by the stepped-wedge design, which may have induced selection bias.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the comparable Spanish EIRA trial [ 35 ] implemented a lifestyle intervention on an individual, group-based and community level. Although it was, like our study, not cost-effective [ 17 ], it showed positive outcomes on lifestyle behaviour in the intervention group on a population level. The personalised approach based on stage of motivation may have contributed to the positive effects of the EIRA trial, where in our study, one group-based programme was offered for all.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, people are interrupted from the outside in their unhealthy lifestyle and a health-promoting strategy is tried to be implemented. However, interventions are expensive [12][13][14], and still commonly reach only a relatively small proportion of individuals [15]. Approaches and attempts to scale up interventions to promote physical activity [16] and healthy eating [17] are encouraging.…”
Section: Proactive Behavior Change Techniques (Probcts) In Physical A...mentioning
confidence: 99%
“…The EIRA study [ 13 ], through a hybrid trial, evaluates, as the main objective, the cost-effectiveness and implementation of a complex intervention that addresses multiple lifestyles (diet, physical activity and smoking) to promote healthy behaviours in a large sample of patients between 45 and 75 years of age attended in primary healthcare. The full trial results were published separately [ 14 , 15 ]. This manuscript reports the effectiveness of this intervention to increase adherence to the MD.…”
Section: Introductionmentioning
confidence: 99%